Evaluation of polyherbal synergy against diabetes: in-vitro analysis - Sridevi N.; Thirumal M. (Future Science OA)
Aims To evaluate the anti-diabetic properties of a polyherbal formulation consisting of Curcuma longa, Emblica officinalis, and Trigonella foenum-graecum through in-vitro assays, and investigate its synergistic effects on glucose metabolism, lipid metabolism, and insulin function.Materials and methods The polyherbal extract was prepared using methanol, water, and methanol-water as solvents. In-vitro antioxidant (DPPH, Phosphomolybdenum) and anti-diabetic (α-amylase, α-glucosidase inhibition, yeast glucose uptake, and inhibitory glucose diffusion) assays were conducted. L6 rat skeletal muscle cells were used for MTT assay and glucose uptake.Results The methanol extract showed the highest antioxidant and anti-diabetic activities compared to aqueous and hydroalcoholic extracts. The IC50 values in DPPH and α-amylase inhibition assays were close to standard drugs, while the MTT assay demonstrated moderate cytotoxicity, confirming the extract’s safety. Glucose uptake increased significantly, particularly in L6 cells treated with the methanolic extract.Conclusion The polyherbal formulation exhibited potent anti-diabetic properties, particularly the methanolic extract, showing significant glucose regulation and insulin function improvement. This formulation holds promise as a natural treatment for diabetes.